Survival Outcomes for Adolescent and Young Adults With Cancer in Low- and Middle-Income Countries: A Systematic Review - Krista Ariello; Abdel-Nabi Hadi; Avram Denburg; Sumit Gupta (JCO Global Oncology)
PURPOSEPatients with adolescent and young adult (AYA) cancer are recognized as a vulnerable subpopulation in high-income countries (HICs). Although survival gaps between HIC and low- and middle-income country (LMIC) children with cancer are well described, LMIC AYAs have been neglected. We conducted a systematic review to describe cancer outcomes among LMIC AYAs.METHODSWe captured English language studies published from 2010 onward reporting LMIC AYA cancer survival outcomes. LMICs were defined according to World Bank 2019 classifications, whereas AYAs were defined as diagnosed between age 15 and 39 years. Cohorts were considered AYA if >75% of patients were AYA, the mean/median age and standard deviation were between 15 and 39 years, or the range was within 5 years of the AYA range (ie, 10-45 years). Cohort characteristics were abstracted, including country, cancer type, and cancer outcomes.RESULTSOf 6,207 studies identified by the search strategy, 658 underwent full-text review; 60 met inclusion criteria. No low-income countries were represented. Forty-four (73.3%) studies were conducted in upper-middle–income countries (UMICs) although these represented only 12 of 55 countries currently classified as UMICs. The most common cancers studied were acute lymphoblastic leukemia (n = 13 studies), breast cancer (n = 5), and osteosarcoma (n = 3). Five-year overall survival was highly variable, ranging from 39% to 63% for ALL, 60%-85% for breast cancer, and 47%-83% for osteosarcoma.CONCLUSIONAlthough three billion AYAs reside in LMICs, their cancer outcomes are neglected in the current literature. Existing data indicate variable survival, ranging from comparable with HIC outcomes to substantially inferior. These studies, however, represent only a limited number of LMICs and are biased toward UMICs. Systematic efforts to describe and improve LMIC AYA cancer outcomes are required.